PENERAPAN POLA HIDUP BERSIH DAN SEHAT (PHBS) DALAM RANGKA MENGANTISIPASI DAMPAK COVID-19 LINGKUP ANAK JEMAAT MARTURIA OESAPA SELATAN, KOTA KUPANG - Deviarbi Sakke Tira; Agus Setyobudi; Enos Kabu (Pergizi Pangan DPD NTT, 2023)
Corona Virus Disease 2019 (Covid-19) is a disease outbreak that spreads widely throughout the world, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARSCoV-2) virus infection. In dealing with this Covid-19 outbreak, it is necessary to change the attitude of everyone in terms of maintaining their body health. Clean and Healthy Living Behavior (PHBS) is highly recommended to be implemented because maintaining body immunity is very important so that the body remains healthy and avoids disease; however, there are still very many citizens who do not understand the importance of PHBS, especially among young people (children and adolescents) in Kupang City). This service activity aims to provide a thorough understanding of PHBS to young people so that it can be applied in their daily lives. The method of implementing this community service activity begins with data collection using an exploratory approach with a combination of observation and crosscectional study designs, namely all data collected in one period of time accompanied by field observations and recording. Furthermore, counseling is carried out which is accompanied by a form of pre and post test evaluation to measure changes in participants' attitudes about the counseling material, namely the implementation of the PHBS program. Overall, the activities were carried out well, participants knew well about Covid-19 disease and how to prevent it, healthy food, using masks and how to wash hands properly. However, in terms of their knowledge of Covid-19 disease, most participants only mentioned what Covid-19 disease stands for, how to wash their hands and how to use masks. The participants could only mention the reason for practicing handwashing, namely